AN IMPLIED METAPHOR - Karjawbaev Orazali Esbosinuli; Toleubayeva A.O (TADQIQOTLAR.UZ, 2024)
Abstract: A sort of metaphor known as an inferred metaphor contrasts two dissimilar objects without specifically naming one of them. "Elise finally lured Adam into her web," for instance. Although it isn't said explicitly, we are aware of the comparison Elise is making with a spider in the is statement. You'll notice that implied metaphors differ slightly from ordinary metaphors in that they don't expressly specify what they're comparing when you examine examples of them. For instance, the line "My Dad is my rock" compares a parent to something substantial and unwavering. This is very different from the statement, "Harry crumbled under the pressure," which suggests the guy was unable to handle pressure by drawing comparisons to things that break readily, such as cakes, soft cheeses, or even falling rocks. You are free to draw your own conclusion son this one. With implied metaphors, authors may evoke strong visuals in their writing. There are instances when the parallel is obvious and a simple jump to make. At other instances, the inferred analogy pauses. Since the author never states these inferred analogies explicitly, they are in fact completely debatable.